The Impact of Marketing Mix Towards Customer Satisfaction in The Case of Sushi Tei Surabaya - Randy Alexander (iBuss Management, 2019)
The Importance of effective marketing in order to stay competitive and relevant in the modern era, especially digital revolution. This research is being conducted in order to understand better, the impact of Marketing Mix towards Customer Satisfaction. Marketing Mix will be used as a variable which will be represented by Product, Price, Place, and Promotion towards Customer Satisfaction in Sushi Tei Surabaya.The research will utilize simple random sampling, distributed via online questionnaire in order to gather data from Sushi Tei customers. Then, the data that has been acquired is being tested for their validity & reliability, Classical Assumption Test, and finally through Multiple Linear Regression. The findings of the research suggest that Marketing Mix as a whole do have an impact towards Customer Satisfaction. From those 4Ps, Product is the most impactful factor, followed by Price, Place, and Promotion.            Key words: Marketing Mix, 4P, Customer Satisfaction, SushiTei